Validation of Blood Pressure Measurement Using a Smartwatch in Patients With Parkinson's Disease - Ahn, Jong Hyeon; Song, Joomee; Choi, Inyoung; Youn, Jinyoung; Cho, Jin Whan (Frontiers in Neurology, 2021)
Objectives: We aimed to validate the accuracy of blood pressure (BP) measurement using a smartwatch in patients with Parkinson's disease (PD). Materials and Methods: We compared 168 pairs of BP (n = 56) measurements acquired by a smartwatch (SM-R850) with those measured by a sphygmomanometer (reference device). Results: Differences between the smartwatch BP and reference BP measurements were compared. The mean and standard deviation of the differences systolic BP (SBP) and diastolic BP (DBP), measured by smartwatch and reference device, fulfilled both criterion 1 (0.4 ± 4.6 and 1.1 ± 4.5 mm Hg for DBP and SBP, respectively) and criterion 2 (0.2 ± 2.5 and 0.9 ± 2.4 mm Hg for DBP and SBP, respectively) of the BP validation criterion of the International Organization for Standardization. Conclusion: BP measurement using a smartwatch with a photoplethysmography sensor is an accurate and reliable method in patients with PD.